A Produksi Serasah Hutan Mangrove di Nagari Pilubang, Kecamatan Sungai Limau, Kabupaten Padang Pariaman : Produksi Serasah Hutan Mangrove di Nagari Pilubang, Kecamatan Sungai Limau, Kabupaten Padang Pariaman - Pratiwi, Amanda Elza (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Litter is organic material that falls into the surrounding waters or soil and is an important part of the fertility of the mangrove ecosystem in the transfer of organic material from vegetation into the soil. The aim of this research is to determine the amount of mangrove forest litter production in Nagari Pilubang, Kecamatan Sungai Limau, Kabupaten Padang Pariaman. This research is descriptive in nature and was carried out from January-April 2024. The litter production method used was the litter-trap method. Mangrove litter collection was carried out at 3 predetermined research stations with 3 sub stations each. Then 3 litter-traps measuring 1x1 m2 were installed at each station which were installed under the canopy of the mangrove stand at a height of 1 - 1.5 m above ground level. The litter production samples were taken within 10 days 6 times and then placed in the oven at 80oC until the weight was constant. Then the litter mass calculation was carried out within 2 months. The results of this research show that the average litter production in the Nagari Pilubang, Kecamatan Sungai Limau, Kabupaten Padang Pariaman is 5.31 gr/m2/day.